Neonatal Resuscitation With T-Piece Systems: Risk of Inadvertent PEEP Related to Mechanical Properties - Drevhammar, Thomas; Falk, Markus; Donaldsson, Snorri; Tracy, Mark; Hinder, Murray (Frontiers in Pediatrics, 2021)
Background: Resuscitation of newborn infants using T-piece resuscitators (TPR) allow positive pressure ventilation with positive end-expiratory pressure (PEEP). The adjustable PEEP valve adds resistance to expiration and could contribute to inadvertent PEEP. The aim was to investigate the risk of incomplete expiration when using TPRs by determining the system expiratory time constants in a mechanical model simulating newborn lungs. Methods: We used adiabatic bottles to generate four levels of compliance. Expiratory time constants were recorded for combinations of fresh gas flow (8, 10, 15 L/min), PEEP (5, 8, 10 cm H2O), airway resistance (50, 200 cm H2O/L/sec and none), endotracheal tube (none, size 2.5, 3.0, 3.5 and none) and compliance (0.5 to 3.4 mL/cm H2O) with a peak inflation pressure 15 cm H2O over PEEP. Results: Low compliances resulted in short time constants but with higher compliances the expiratory time constants were 0.25 to 0.81 s. Increased time constants were seen for increased resistance due to lower fresh gas flows, higher set PEEP levels, with an added airway resistance or endotracheal tube. Conclusions: The risk of inadvertent PEEP increases with a shorter time for expiration in combination with a higher compliance and resistance. The TPR resistance can be reduced by increasing the fresh gas flow or reducing PEEP. The recorded expiratory time constants indicate that this may be clinically important. The risk of inadvertent PEEP would be highest in term infants with compliant lungs. These results are useful for interpreting clinical events and recordings.